Optimalisasi Sistem Manajemen untuk Meningkatkan Kualitas Pelayanan Publik: Studi Kasus di Kelurahan Nongkosawit, Kecamatan Gunungpati, Kotamadya Semarang - Sapto Supriyanto; Bambang Guritno; Hartoyo Soehari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Nongkosawit Village, which is located in Gunung Patti District, Semarang City, aims to improve the quality of services to the local community by implementing an optimal management system. This research aims to understand and analyze key factors that influence community satisfaction with Nongkosawit Village services, such as management, service quality, and the village's important role as a public service provider. This research identifies several problems that influence service quality in Nongkosawit District and investigates the impact of service quality on community satisfaction. A comprehensive problem-solving approach is applied, emphasizing the impact of employee competency and service facilities. Furthermore, this research explores the novelty in implementing modern management practices related to the characteristics of Nongkosawit Village. The research roadmap for the next five years is designed to implement concrete steps such as improving workforce skills, upgrading service facilities, and integrating information technology. This phase includes needs analysis and service quality assessment, improving employee skills, updating service facilities, integrating information technology, as well as ongoing evaluation and maintenance. It is hoped that the results of this research will make a major contribution to improving the quality of services in Nongkosawit Village and provide a theoretical and practical basis for further research and development. Therefore, it is hoped that this research will be able to formulate innovative solutions to support community satisfaction through improving the quality of public services in Nongkosawit Village.